The honey-don't list ebook - Lauren, Christina (2020)
From the New York Times bestselling author behind the "joyful, warm, touching" (Jasmine Guillory, New York Times bestselling author) The Unhoneymooners comes a delightfully charming love story about what happens when two assistants tasked with keeping a rocky relationship from explosion start to feel sparks of their own. Carey Duncan has worked for home remodeling and design gurus Melissa and Rusty Tripp for nearly a decade. A country girl at heart, Carey started in their first store at sixteen, and—more than anyone would suspect—has helped them build an empire. With a new show and a book about to launch, the Tripps are on the verge of superstardom. There's only one problem: America's favorite couple can't stand each other. James McCann, MIT graduate and engineering genius, was originally hired as a structural engineer, but the job isn't all he thought it'd be. The last straw? Both he and Carey must go on book tour with the Tripps and keep the wheels from falling off the proverbial bus. Unfortunately, neither of them is in any position to quit. Carey needs health insurance, and James has been promised the role of a lifetime if he can just keep the couple on track for a few more weeks. While road-tripping with the Tripps up the West Coast, Carey and James vow to work together to keep their bosses' secrets hidden, and their own jobs secure. But if they stop playing along—and start playing for keeps—they may have the chance to build something beautiful together... From the "hilariously zany and heartfelt" ( Booklist ) Christina Lauren comes a romantic comedy that proves if it's broke, you might as well fix it.